Oxidative Stress Association with Autonomic Dysfunction in Parkinson Patients - Hamod, Asma'a Khalaf; AL- Khazraji, Abdul Kareem Kadim; Ja'afer, Isra'a Fayiq; Hamdan, Farqad Badar (Diyala Journal of Medicine, 2019)
Background: Parkinson’s disease may be caused by oxidative stress within cells due to defective nucleoli. Dopamine producing neurons are particularly sensitive to oxidative stress. The researcher's present evidence showing defective nucleoli within dopamine producing neurons lead to oxidative stress and damage Objective: To assess antioxidant activity in Parkinson patients with autonomic dysfunction. Materials and Methods: samples were collected in Al Kadhimiya Teaching hospital and Baquba teaching hospital in a period lasts from 1st January to 1st November 2013. Antioxidant activity had been tested in 44 Parkinson patients with autonomic dysfunction, 23 Parkinson patients without autonomic dysfunction and 25 healthy matched controls; using (Antioxidant Capacity, Total BioAssay™ Kit ;US Biological company, Catalog No. A2298-43). Results: antioxidant activity showed a reduction in its level in Parkinson patients without autonomic dysfunction (0.75) with further reduction in Parkinson patient with autonomic dysfunction (0.37) compared with the control groups (1.2). Conclusion: Oxidative stress and antioxidants have a role in pathogenesis of Parkinson disease. Both increase oxidative stress (direct) and a reduction in activity of the antioxidants (indirectly) cause loss of neuron and reinforcing damage mechanisms that play a role in autonomic dysfunction in Parkinson Disease.